2020
DOI: 10.1142/s0217984920503959
|View full text |Cite
|
Sign up to set email alerts
|

Study thermodynamic assessment of the B-C and B-Si binary systems with swift heavy ions and high intense electron beam irradiation at the low temperature

Abstract: B4C and B6Si samples have been irradiated by using swift heavy ions and high intense electron beam. Ion irradiation of the samples was carried at the different electron fluences [Formula: see text], [Formula: see text] and [Formula: see text] cm[Formula: see text] ion/cm2, and energy of ions flux 167 MeV. Also, the samples were irradiated with high energy electron beams at the linear electronic accelerator at different electron fluencies up to [Formula: see text] cm[Formula: see text] and energy of electron be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The change in the peak position can be due to the lattice disorder (lattice expansion) in the crystal structure and the stress introduced by the SHI irradiation ( Figure 1 b—Zone A) [ 49 , 50 , 51 ]. According to L. Desgranges et al [ 52 ], displacement of X-ray diffraction spectra was observed in a sample of B 4 C boron carbide irradiated with thermal neutrons.…”
Section: Swift Heavy Ion Irradiation: X-ray Diffractionmentioning
confidence: 99%
“…The change in the peak position can be due to the lattice disorder (lattice expansion) in the crystal structure and the stress introduced by the SHI irradiation ( Figure 1 b—Zone A) [ 49 , 50 , 51 ]. According to L. Desgranges et al [ 52 ], displacement of X-ray diffraction spectra was observed in a sample of B 4 C boron carbide irradiated with thermal neutrons.…”
Section: Swift Heavy Ion Irradiation: X-ray Diffractionmentioning
confidence: 99%